A new species of giant gecko of the genus Rhacodactylus from New Caledonia (Squamata, Gekkota, Diplodactylidae) - Köhler, Gunther; Sameit, Joachim; Seipp, Robert; Geiss, Katharina (Zootaxa, 2024)
We describe a new species of giant gecko, Rhacodactylus willihenkeli sp. nov. from New Caledonia. The new species is most similar in external appearance and molecular data (16S and ND2 sequences) with R. leachianus from which it differs in coloration as well as having a genetic distance of 5.0% in the 16S gene fragment and 8.5% in the ND2 fragment, respectively.